2019
DOI: 10.1590/0100-3984.2018.0128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between right atrium area and right ventricular ejection fraction on magnetic resonance imaging: comparison with other prognostic markers in patients with pulmonary arterial hypertension

Abstract: Objective: To compare the right atrium (RA) area and right ventricular ejection fraction (RVEF) with other known prognostic markers in patients with pulmonary arterial hypertension (PAH). Materials and Methods: This was a retrospective study of 74 patients diagnosed with PAH by right heart catheterization at a referral center between January 2018 and May 2018. All of the patients underwent cardiac magnetic resonance imaging (MRI) within 3 months of the right heart catheterization (RHC), as well as undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Circulating levels of natriuretic peptides mirror myocardial stress due to pressure and volume overload and are established diagnostic and prognostic markers in heart failure 29 12 associated with secondary right heart failure and assessment of these biomarkers is recommended for screening, individual risk stratification, and therapy monitoring 30 . The current study found a strong correlation of NT-proBNP with right ventricular dimensions and function prior to BPA therapy, which is in line with the findings from other series 26,31 . The current guidelines on PH suggest an NT-proBNP level >300 ng/L as a cut-off to distinguish low-risk and elevated-risk patients 30 .…”
Section: Cmr and Biomarker Findings At Baselinesupporting
confidence: 92%
See 2 more Smart Citations
“…Circulating levels of natriuretic peptides mirror myocardial stress due to pressure and volume overload and are established diagnostic and prognostic markers in heart failure 29 12 associated with secondary right heart failure and assessment of these biomarkers is recommended for screening, individual risk stratification, and therapy monitoring 30 . The current study found a strong correlation of NT-proBNP with right ventricular dimensions and function prior to BPA therapy, which is in line with the findings from other series 26,31 . The current guidelines on PH suggest an NT-proBNP level >300 ng/L as a cut-off to distinguish low-risk and elevated-risk patients 30 .…”
Section: Cmr and Biomarker Findings At Baselinesupporting
confidence: 92%
“…29 The current study found a strong correlation of NT-proBNP with right ventricular dimensions and function prior to BPA therapy, which is in line with the findings from other series. 25,30 The current guidelines on PH suggest an NT-proBNP level >300 ng/L as a cut-off to distinguish low-risk and elevated-risk patients. 29 Consistent with this, patients in our cohort with a severely impaired RVEF were identified by an NT-proBNP level !347 ng/L and showed a median level of 1427 ng/L at baseline, whereas patients with an RVEF > 35% had a median level of 214 ng/L.…”
Section: Cmr and Biomarker Findings At Baselinementioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Radiologia Brasileira, readers will find an interesting article authored by Mello et al (9) , who studied the relationship between the right atrium area and the RV ejection fraction by MRI, in comparison with other prognostic markers, in patients with PAH. In their study, the authors found that the RV ejection fraction and the right atrium area determined by cardiac MRI both correlated with clinical prognostic markers.…”
mentioning
confidence: 99%